Research of the Operation Characteristic of New Type CVT System Used in Heavy Duty Drilling Automation Platform - Zhang Juan; Fan Minglong (Jixie chuandong)
In order to solve the problems of difficult arrangement,high production cost of drilling automation platform transmission system in the heavy duty condition,a new CVT system of drilling automation platform is introduced by analyzing the new type layout scheme of CVT structure,working principle and key performance indicators,and the influence of the differential mechanism transmission ratio of the new CVT system on the torque distribution ratio,output and input torque ratio of the new system and the influence of the reducing mechanism transmission ratio on the torque distribution ratio of the new system are calculated. Finally,the feasibility of new type CVT system of heavy duty drilling automation platform is validated by the test method. The results show that,the reduction mechanism transmission ratio and differential mechanism ratio have great influences on the property of the new type CVT system parameters,with the introduction of the new type CVT system into drilling automation platform,the each measuring point stress maximum value and fluctuation value are decreased,which can obviously improve the system safety and smooth running.